2009
DOI: 10.1093/jleo/ewn027
|View full text |Cite
|
Sign up to set email alerts
|

Should Firms be Allowed to Indemnify Their Employees for Sanctions?

Abstract: Abstract:Policymakers have questioned whether firms should be allowed to indemnify their employees for personal sanctions for corporate crimes. This paper provides the first formal analysis of this form of indemnification. Indemnification should typically not be banned because of the relative benefits it offers to law-abiding firms: insuring employees against the risk of mistaken government prosecution, strengthening employees' resolve to fight meritless suits. Only in limited circumstances do we find banning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Forbidding indemnifi cation removes an instrument that would be used in a contract to induce crime. Nevertheless, Mullin and Snyder (2009) show that forbidding indemnifi cation is socially ineffi cient. The result follows from employee risk aversion.…”
Section: Agent Indemnifi Cationmentioning
confidence: 99%
“…Forbidding indemnifi cation removes an instrument that would be used in a contract to induce crime. Nevertheless, Mullin and Snyder (2009) show that forbidding indemnifi cation is socially ineffi cient. The result follows from employee risk aversion.…”
Section: Agent Indemnifi Cationmentioning
confidence: 99%
“…Collusion may cause managers a non‐monetary, per‐period opportunity cost κ that is not incurred when competing or deviating. This dis‐utility is modeled as an opportunity cost parameter that is additively separable from the utility gained from profits (Mullin and Snyder, ; Krupka and Weber, ; Huck et al, ) as is shown by Equation . uk,κ=u(),,skkκ …”
Section: Modelmentioning
confidence: 99%
“…For instance, outcome-based contracts as a means to mitigate the behavior-verification problem (Eisenhardt, 1989) can increase the expected benefits of crime by incentivizing agents to use whatever tactics necessary, including illegal ones, to achieve performance goals (Ordóñez, Schweitzer, Galinsky, & Bazerman, 2009). Conversely, contractual clauses intended to mitigate agents' (i.e., managers') presumed aversion to risk (Eisenhardt) can decrease the expected costs of crime, particularly when they indemnify agents against sanctions for criminal activity (Margulies, 2006;Mullin & Snyder, 2010;Orland, 1979). In sum, attempts to resolve classic agency problems may unintentionally induce another: corporate crime.…”
Section: Corporate Crime As An Agency Problemmentioning
confidence: 99%